p + 4 - 2 (p - 10) > 0

Question

Asked 7/22/2012 3:08:20 AM

Updated 250 days ago|1/12/2018 12:16:22 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [1/12/2018 12:13:56 PM]

Jodynoel613|Points 10|

danimai|Points 1504|

bongche|Points 2665|

Question

Asked 7/22/2012 3:08:20 AM

Updated 250 days ago|1/12/2018 12:16:22 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [1/12/2018 12:13:56 PM]

Rating

3

p + 4 - 2 (p - 10) > 0

= - p + 24 > 0

= - p >0 - 24

= - p > - 24

= p > - 24/-1

= p < 24

= - p + 24 > 0

= - p >0 - 24

= - p > - 24

= p > - 24/-1

= p < 24

Added 250 days ago|1/12/2018 12:13:55 PM

This answer has been confirmed as correct and helpful.

3

4x + 6 < -6

4x < - 6 - 6

4x < - 12

x < - 12/4

x < - 3

4x < - 6 - 6

4x < - 12

x < - 12/4

x < - 3

Added 250 days ago|1/12/2018 12:14:42 PM

This answer has been confirmed as correct and helpful.

3

12x - 3x + 11 > 4x - (17 - 9x)

9x + 11 > 13x - 17

9x + 11 > 17 - 13x

- 4x + 11 > - 17

- 4x > - 17 - 11

- 4x > - 28

x > - 28 / -4

x < 7

9x + 11 > 13x - 17

9x + 11 > 17 - 13x

- 4x + 11 > - 17

- 4x > - 17 - 11

- 4x > - 28

x > - 28 / -4

x < 7

Added 250 days ago|1/12/2018 12:16:22 PM

This answer has been confirmed as correct and helpful.

27,351,297

questions answered

There are no comments.